STUDY ON FUNCTIONAL FACILITIES UTILIZATION OF CAROCOK TARUSAN FISHING PORT PROVINSI SUMATERA BARAT - Aryani, Nova; Sari, T. Ersti Yulika; Zain, Jonny (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT The purpose of this study was  to determine the level of utilization of functional facilitiesin PPP Carocok Tarusan. This research was conducted on July 2018 at PPP Carocok Tarusan, West Sumatra. The method used in this study is the survey method, which is by making observations and collecting data directly regarding the utilization of PPP functional facilities. Based on the results of the study, the functional facilities in PPP Carocok Tarusan include TPI, fresh water tanks, fuel tanks, fish processing buildings, generator buildings, workshops, satellite buildings, and catching materials stores. But of all the functional facilities that are still functioning to support servicing activities at PPP Carocok Tarusan, there is only one (1) facility that can be calculated because the facility is used according to its function, which are a freshwater tank facility, while facilities are utilized not according to its function and facilities that are not utilized which are calculated is the size of facilities needed, namely TPI facilities, and fuel tanks. Based on the results of the analysis, the value of the utilization rate of freshwater tank facilities is 6.05%, which means it is not very good. Based on the results of the analysis, if the auction activity is carried out in TPI, the total area needs 186,397 m3. The fuel tank capacity of the required facilities is 8,915 m3. Genset building facilities, workshop facilities and shop facilities Materials and fishing equipment in good condition and functioning according to their functions, satellite building facilities are currently lightly damaged but still functioning according to their functions and fish processing facilities are currently damaged and not functioning anymore and need to be built an ice plant with a requirement of 410 beams / day, it requires an ice plant capacity of 615 tons.Key words : Carocok Tarusanfishing port, functional facilities, utilization level